Antimicrobial resistance in orthopedics: microbial insights, clinical impact, and the necessity of a multidisciplinary approach—a review - Julia L van Agtmaal; Mariëlle Verheul; Lieve Vonken; Kato Helsen; Marian G Vargas Guerrero; Sanne W G van hoogstraten; Bianca J Hurck; Giulia Pilla; Isabell Trinh; Gert-Jan de Bruijn; Henrik P Calum; Mark G J de Boer; et al. (Acta Orthopaedica, 2025)
Antimicrobial resistance (AMR) is rising globally and is a threat and challenge for orthopedic surgery, particularly in managing prosthetic joint infections (PJIs). This review first explores several AMR mechanisms from a microbiological point of view, including selective pressure, horizontal gene transfer, and further dissemination. Second, the variation in the rise of AMR across countries is highlighted, including its impact on PJI. While countries with the highest AMR rates are expected to experience the most significant burden, no country will be immune to the increasing prevalence of PJI. Third, this review stresses that multidimensional strategies are needed to combat AMR’s challenges in orthopedic surgery. These include raising awareness across all sectors, including healthcare professionals, the public, healthcare policymakers, and even politicians; advancing diagnostic technologies for early infection detection and classification of resistant or susceptible strains; promoting antibiotic stewardship; and developing new material technologies to prevent or cure PJI. This review highlights the urgent need for a coordinated response from clinicians, researchers, and policymakers to avoid AMR-related complications in PJI cases.